ASSISTANCE FOR MA PP SHEIKH ANDURRAHMAN RABAH TEACHERS IN USING THE IMAGINATION SUGGESTION LESSON METHOD TO INCREASE STUDENT CREATIVITY - Alfiansyah, Alfiansyah (TOPLAMA, 2024)
This research aims to support teachers at MA PP Syekh Andurrahman Rabah in utilizing the Imagination Suggestion method to enhance student creativity. The study employed a qualitative approach, specifically action research, involving multiple cycles of training, mentoring, and classroom implementation. Data were collected through observations, interviews, and analysis of student works to evaluate the impact of this method on creativity. The findings indicate that after receiving training, teachers demonstrated increased confidence and proficiency in applying the Imagination Suggestion method across various subjects, including mathematics and science, which were initially perceived as less suitable for creative approaches. Moreover, students exhibited notable improvements in creative thinking skills, including divergent thinking, problem-solving flexibility, and the willingness to express new ideas. The research highlights the positive correlation between the implementation of the Imagination Suggestion method and the development of creativity among students, suggesting that an imaginative and supportive learning environment fosters greater engagement and innovation. Ultimately, this study provides significant insights into the importance of integrating creative teaching methods in educational practices, particularly in madrasah settings. The research concludes by offering recommendations for other educational institutions to adopt similar innovative approaches to enhance student creativity.